Implementing mixed augmented and virtual reality in an animated flipped classroom for low-achieving writers in rural primary schools - Jalaluddin, Ilyana; Darmi, Ramiza; Ismail, Lilliati (Universiti Malaysia Sarawak, 2024)
The study examined the implementation of mixed augmented and virtual reality in an animated flipped classroom for low-achieving writers in rural primary schools. A quasi-experimental study employing a pre-post, non-equivalent control group design was conducted. In a flipped classroom, students use digitised or online lectures as pre-class homework, then engage in active learning process in the classroom such as peer teaching, projects, problem solving and group activities. In other words, the typical classroom of lecturing only during class time is “flipped” now to active activities that involve problem solving and group project work in class. Results show that this flipped learning approach improves rural learners’ proficiency, particularly in vocabulary acquisition. It was found that there was a statistically significant difference in vocabulary level between trials at the midway time point. Apart from that, there is a statistically significant difference in the vocabulary level in the intervention trial at the end (post) of the trials. However, successful implementation of this technology necessitates a comprehensive approach considering cultural and infrastructural factors.